San Roman to head Guard unit (Raton Range Raton, New Mexico, 1989)
Newspaper Article on Captain Gilbert N. SanRoman and becoming the new commander of the 2nd Battalion, 1st Infantry Brigade of the New Mexico State Defense Force in Raton, New Mexico.
Master list item #: 10
File location is in the Raton File Cabinet
Keywords: SanRoman, Gilbert N; National Guard; U.S. Air Force; Army National Guard; New Mexico State Defense Force; Department of Military Affairs; Local History; Biography; Life and Customs; Firefighter; National Guard; State Defense Force; Volunteers; Raton, New Mexico; Roswell, New Mexico